Case Study Method dan Problem Based Learning Sebagai Model Pembelajaran Digital terhadap HOTS Learning Guru Akuntansi di Masa Era Revolusi Industri 4.0 - OK Sofyan Hidayat; Azizul Kholis; La Hanu; Choms Gary G.T. Sibarani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to develop innovative and creative accounting learning for teachers as future educators in facing the industrial revolution 5.0 based on case studies and problem-based learning. The problem is focused on elaborating and exploring in depth the ideal contemporary accounting learning approaches, models and strategies and the preparation of future learning models as prototypes. To approach this problem, theoretical references from case studies and problem-based learning are used. questionnaire and analyzed qualitatively. This study concludes that the application of the case study method and problem-based learning model can be applied as a digitalization-based learning model at SMK in North Sumatra. This is evidenced from research data which shows that most teachers, schools and students have readiness in applying case study methods and problem-based learning. Learning activities are indicated by an increase in positive activity and a decrease in negative activity in each cycle. Meanwhile, student learning outcomes are indicated by an increase in the average grade value and student learning completeness in each cycle